Development of a Wireless Power Transfer Circuit Based on Inductive Coupling - Supriyadi Supriyadi; Edi Rakhman; Suyanto Suyanto; Arif Rahman; Noor Cholis Basjaruddin (Universitas Ahmad Dahlan, 2018)
Wireless electrical energy transfer has many advantages over the same through conducting cables. This research focusses on developing wireless power transfer circuitusing inductive coupling. The experiment has been done by changing the number of turns and the diameter of the wire of a coil with the aim of finding the maximum power and the longest distancethat the energy can be transferred through wireless means. The power source is connected to a series of electronics components and a copper coil which form the primary source for the transmitter the power receiver consists of a copper coil, a rectifier and the load. In a system with the diameter of the wires of the two coils is0.5 mm, and the number of turns is 26 at the frequency of 470KHz the efficiency of power transfer about 1.51% at a distance of 1 cm. The transferred energy by wireless means could operate a 1 Watt LED at 1 cm.